The Role of Master Teacher of Islamic Society Nahdlatul Wathan in Lombok in Religious and Social Teachings (Islam) - Mawalidin, Jun (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2021)
AbstractThe teachings of Islam for sasak people get a very high place in carrying out their daily religious life in accordance with the religious doctrines embraced. The teachings of Islam for sasak people get a very high place in carrying out their daily religious life in accordance with the religious doctrines embraced. In the content of this scientific work is done by looking at the results of other scientific works. Nahdlatul Wathan focuses on three areas of development, namely education, social and da'wah. The presence of Mr. Guru on the island of a thousand mosques gives a different nuance. Bahklan is a characteristic for the community. Its influence can be felt in various fields, not only in education, in politics but also in the executive field. Keywords: Tuan Guru, Sasak, Islam, Nahdlatul Wathan.